Autobiografía y educación en Mis maestros y mi educación de Federico Rubio y Galí - Marie-Hélène Soubeyroux (Cahiers de Civilisation Espagnole Contemporaine)
A physician and a politician (Member of Parliament and ambassador in London during the First Republic), Federico Rubio y Galí (1827-1902) is also the author of memoirs (Mis maestros y mi educación) which, although they appear in F. Duran Lopez’s catalogue, have never been studied so far. This article seeks to establish the singularity of Rubio’s work in the memorialist tradition of the time, as both a first-person narrative composed of brief sequences in which the aged narrator conjures up the first sensory experiences of his childhood and traces the awakening of his consciousness, and a social and political chronicle of the 1830s in Andalusia construed with an educational purpose. In a second part, the paper analyzes the pedagogical project proposed by a late nineteenth-century intellectual recalling his own experience as a primary-school teacher and criticizing the institution from the enlightened perspective of the pedagogical theorizing carried out within the ILE. This pedagogical project is at the intersection between the private dimension of the memoirs and their public dimension as a reformer’s work anticipating the regenerationist school.